2016
DOI: 10.1371/journal.pone.0164198
|View full text |Cite
|
Sign up to set email alerts
|

Wild Herbivore Grazing Enhances Insect Diversity over Livestock Grazing in an African Grassland System

Abstract: Southern Africa’s grassland biodiversity is threatened by habitat transformation such as commercial forestry. Ecological networks (ENs) have been instigated to alleviate the pressure of habitat transformation on local biodiversity. ENs are large scale webs of corridors and patches of natural vegetation criss-crossing production landscapes that can simulate conditions in protected areas (PAs). Many ENs have lost many native large mammal species, which have been replaced by domestic livestock to retain natural g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…In addition, we expected the presence of domestic mammals to have a negative effect on wild mammals, either directly via competition for the same resources and space, or indirectly via the transmission of diseases (Pryke, Roets, & Samways, ). However, we found a positive effect of the community biomass of domestic mammals on the species richness of wild mammals.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we expected the presence of domestic mammals to have a negative effect on wild mammals, either directly via competition for the same resources and space, or indirectly via the transmission of diseases (Pryke, Roets, & Samways, ). However, we found a positive effect of the community biomass of domestic mammals on the species richness of wild mammals.…”
Section: Discussionmentioning
confidence: 99%
“…The absence, and even the reduction, of grazing and/or the abandonment of previously grazed grasslands has been reported to negatively affect dung beetle communities in other regions (Tonelli et al, 2017;Numa et al, 2009;Verdú et al, 2007Verdú et al, , 2000Lobo et al, 2006). However, Pryke et al (2016) found higher dung beetle diversity in areas grazed by wild animals when compared with areas grazed by domestic animals in Africa. Dung beetles depend on the vertebrate fauna (Estrada et al, 1999), especially large mammals (Barlow et al, 2010), for their food resource, so differences among regions as to the impact of cattle grazing on dung beetle communities may result from differences in the diversity of wild herbivores.…”
Section: Effects Of Cattle Grazing On Patterns Of Abundance Species mentioning
confidence: 97%
“…In contrast to these vertebrate taxa with large home ranges, ground-dwelling beetles have been shown to be particularly sensitive to subtle habitat changes, even at local and small scales (Liu et al, 2016;Pryke, 2016). For example, tenebrionid diversity responded significantly to small spatial changes in plant diversity in a semi-arid, agricultural landscape in Israel (Yaacobi, Ziv, & Rosenzweig, 2007).…”
mentioning
confidence: 99%